Representamen Kebudayaan Jawa; Teknik komparatif referensial pada teks "Wedhatama" - Rahyono, F. X. (Wacana, Journal of the Humanities of Indonesia, 2002)
W dhatama is one of the most famous Javanese literary works. It was written in early 19 th century by K. G. P. A. A. Mangkunagara IV. Its influence in Javanese culture permeates not only the language but also the way of life. The focus of this research in on how, what form and why K. G. P. A. A. Mangkunagara IV conveys his moral message. The study argues that comparative referential technique is used to send a message which is full of moral and lige values, particularly in the concept pf leadership. Furthermore, W dhatama can be seen as a representation of Javanese way of life. This study is paramount in understanding why W dhatama is still relevant for some elements of Javanese society.